Pregunta
\[ f(x) = 3x + 4 \quad g(x) = 2x - 3 \] \[ \text{Find: } f \circ g(x) \]
Ask by Henry Gough. in the United Arab Emirates
Feb 03,2025
Solución de tutoría real
Respuesta verificada por el tutor
Responder
\( f \circ g(x) = 6x - 5 \)
Solución
To find the composition \( f \circ g(x) \), we need to substitute \( g(x) \) into \( f(x) \).
Given:
\[
f(x) = 3x + 4
\]
\[
g(x) = 2x - 3
\]
**Step 1:** Compute \( f(g(x)) \):
\[
f(g(x)) = f(2x - 3)
\]
**Step 2:** Substitute \( g(x) \) into \( f(x) \):
\[
f(2x - 3) = 3(2x - 3) + 4
\]
**Step 3:** Simplify the expression:
\[
3(2x - 3) + 4 = 6x - 9 + 4 = 6x - 5
\]
**Final Answer:**
\[
f \circ g(x) = 6x - 5
\]
Revisado y aprobado por el equipo de tutoría de UpStudy
Como
error msg
Explicar
Simplifique esta solución
Mind Expander
To find \( f \circ g(x) \), we need to substitute \( g(x) \) into \( f(x) \). First, we calculate \( g(x) \): \[ g(x) = 2x - 3 \] Now, we plug \( g(x) \) into \( f(x) \): \[ f(g(x)) = f(2x - 3) = 3(2x - 3) + 4 \] Now, distribute the 3: \[ = 6x - 9 + 4 \] Combine like terms: \[ = 6x - 5 \] Thus, \[ f \circ g(x) = 6x - 5. \]
¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde
Hazte Premium